Modeling Groundwater Surface by MODFLOW Math Code and Geostatistical Method - Ahmad Tahershamsi; Atabak Feizi; Siavash Molaei (Civil Engineering Journal, 2018)
Simulation of groundwater flow by mathematical model can be used for developing aquifer balance element analysis scenarios, explaining conditions of droughts, definition of prohibitive extraction policies and analyzing the qualitative models. In this study, the development of a quantitative model in terms of the main parameters affecting on the water surface changes has been performed for the Ardebil plain (located in NW of Iran). Accordingly, a comprehensive processing of raw data sets has been carried-out by means of MODFLOW mathematical model. Also to simulate the groundwater surface changes in the mentioned plain, the geo-statistical method has been used. Results indicate that the mathematical model used in the aquifer balance simulation for the Ardebil plain has approximately 2% relative normal root-mean-square error (NRMSE). This small NRSMSE confirms the model accuracy for the Ardebil plain using the calibration data. Moreover, comparing the results of this method and the ones obtained by mathematical model performed by examining some error criteria like RMSE, Mean, ASE and MS, it is found that the accuracy of the mathematical model is higher than the geostatistical method and the main reason for this is the distribution of uncertainty in a few available piezometric points in the geostatistical method.